STRATEGI DAN PERSAINGAN PERGURUAN TINGGI SWASTA - Budiyono dan Sri Laksmi Pardanawati (ITB AAS INDONESIA, 2014)
To face the competition of private universities must have the appropriate strategies Strategies that can give direction to the organization to face challenges and threats that arise in the present and the future taking into account its strengths and weaknesses.Keywords: Strategy and Competition